1995
DOI: 10.1002/pd.1970150102
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prenatal diagnosis of 14 cases of triploidy using fish with multiple probes

Abstract: Fluorescence in situ hybridization (FISH) of chromosome-specific probes to interphase nuclei can rapidly identify aneuploidies in uncultured amniotic fluid cells. Using DNA probe sets specific for chromosomes 13, 18, 21, X, and Y, we have identified 14 fetuses where the hybridization pattern was consistent with a triploid chromosome constitution. In each case, the identification of fetal abnormalities by ultrasound examination initiated a request for rapid determination of ploidy status via prenatal FISH analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Male specimens gave a range of 6±100% of nuclei with an XY pattern. A study on 14 uncultured triploid amniotic¯uid samples found a signal pattern for sex chromosomes in agreement with the karyotype in 58±99% of the nuclei (Gersen et al, 1995). In cells from uncultured CVS samples that had attached to a substrate, Bryndorf et al (1996) found that female samples had an average of 99% (44±100%) of their nuclei showing an XX signal pattern, while male samples had an average of 99% (22±100%) of their nuclei showing an XY signal pattern.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Male specimens gave a range of 6±100% of nuclei with an XY pattern. A study on 14 uncultured triploid amniotic¯uid samples found a signal pattern for sex chromosomes in agreement with the karyotype in 58±99% of the nuclei (Gersen et al, 1995). In cells from uncultured CVS samples that had attached to a substrate, Bryndorf et al (1996) found that female samples had an average of 99% (44±100%) of their nuclei showing an XX signal pattern, while male samples had an average of 99% (22±100%) of their nuclei showing an XY signal pattern.…”
Section: Introductionmentioning
confidence: 82%
“…In uncultured normal CVS samples, 98% (36±100%) of nuclei show two signals (Bryndorf et al, 1996). In uncultured trisomic or triploid amniotic¯uid samples, the range of percentages of nuclei with three signals varies widely from 12.5 to 90% (Zheng et al, 1992;Cacheux et al, 1994;Gersen et al, 1995;Bryndorf et al, 1997). For uncultured trisomic CVS samples, Bryndorf et al (1996) found the mean percentages of nuclei with three signals to be 84% with a range of 52±96%.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, the diagnosis of triploidy can be strongly sus pected on the basis of the hematological pic ture. These findings are more readily avail able than with most rapid methods using fluo rescence in situ hybridization [26]. This al lows physicians to immediately counsel par ents about the prognosis of the fetus.…”
Section: ]mentioning
confidence: 92%
“…In cases 1 and 2, FISH was performed because of prior sonographic suspicion, and it was possible to quickly determine in case 1 a trisomy 18 and in case 2 a trisomy of chromosomes X and 18. This means that using centromeric probes simultaneously for several chromosomes in possible to determine the existence of several trisomies [17].…”
Section: Discussionmentioning
confidence: 99%